Depositional Environmental Changes of Cimanceuri Formation Based on Mollusk Fossil Assemblages in Bayah, Banten Province - Rahajeng Ayu Permana Sari; Winantris Winantris; Lili Fauzielly; Anita Galih Ringga Jayanti; Aswan Aswan; Unggul Prasetyo Wibowo (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
Bayah is located in Lebak Regency, Banten Province. This location is chosen due to its abundant mollusk fossils which exposed along the outcrops. The aim of this research is to determine depositional environmental changes using mollusk fossil assemblages. Data obtained from a measured stratigraphic section of Cimanceuri Formation. It is dominated by very fine-fine sandstones with claystone intercalation. A total thickness of measured stratigraphic section is 4.2 meters. There are at least seventeen mollusk associations (bottom-top) consisting of 1) Ringicula arctatoides - Olivella tomlini were obtained. 2) Ringicula arctatoides - Marginella (Cryptospira) ventricosa sangiranensis. 3) Olivella tomlini, 4) Ringicula arctatoides - Olivella tomlini, 5) Ringicula arctatoides, 6) Turritella (Turritella) bantamensis - Scapharca (Scapharca) gedinganensis, 7) Polinices aurantius - Marginella (Cryptospira) ventricosa sangiranensis, 8) Scapharca (Scapharca) gedinganensis, 9) Scapharca (Scapharca) multiformis - Timoclea bataviana, 10) Turritella (Turritella) bantamensis tjicumpaiensis - Ringicula arctatoides, 11) Turritella (Turritella) bantamensis - Ringicula arctatoides, 12) Turritella (Turritella) bantamensis tjicumpaiensis - Turritella (Turritella) bantamensis, 13) Turritella (Turritella) bantamensis tjicumpaiensis - Ringicula arctatoides, 14) Turritella (Turritella) bantamensis - Architectonica sp., 15) Turritella (Turritella) bantamensis tjicumpaiensis, 16) Turritella (Turritella) bantamensis – Turritella (Turritella) bantamensis tjicumpaiensis, and 17) Turritella (Turritella) bantamensis. The condition with the most stable ecosystem is the association of Turritella (Turritella) bantamensis tjicumpaiensis - Turritella (Turritella) bantamensis (Association 12). At least there are seven depositional environmental changes that occur in this research area with two shallowing – deepening cycles : 1) open shallow marine, 2) subtidal – open shallow marine, 3) open shallow marine, 4) open shallow marine – subtidal, 5) subtidal, 6) subtidal – open shallow marine, and 7) open shallow marine.